Republic of Poland : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2003 Article IV Consultation highlights that the economy of the Republic of Poland began to recover during 2002 from the sharp weakening of growth in 2000-01, but the recovery is fragile. Private consumption picked up gradually, fueled by rising real fiscal transfers, easing monetary policy, and a drop in the savings ratio. Exports outpaced rather weak market growth as competitiveness improved. The recovery also reflected a lessening of negative influences: a sharp drop in inventories ended, and the contraction of fixed investment lessened.